Methodology for the synthesis of methacrylate monomers using designed single mode microwave applicators. Issue 8 (8th July 2019) - Dundas, Adam A.; Hook, Andrew L.; Alexander, Morgan R.; Kingman, Samuel W.; Dimitrakis, Georgios; Irvine, Derek J.
Abstract : A novel single-well prototype high throughput microwave reactor geometry has been produced and shown to be capable of synthesizing an array of non-commercially available methacrylate monomers. Abstract : A novel single-well prototype high throughput microwave reactor geometry has been produced and shown to be capable of synthesizing an array of non-commercially available methacrylate monomers. The reactor, which delivers the energy required via a dedicated coaxial line, has been shown experimentally to outperform other conventional/microwave formats. It is demonstrated to achieve significantly higher conversions than the alternative reactor types, whilst requiring (a) low levels of input power, (b) no additional energy for agitation/mass transfer, (c) no solvent and (d) no environmentally impacting thermos-fluids.